Effect of Coolant Temperature on Progressive Freeze Concentration of Refined, Bleached and Deodorised Palm Oil based on Process Efficiency and Heat Transfer (Jurnal Teknologi (Sciences & Engineering), 2015)
In this paper, raw material of refined bleached and deodorised palm oil (RBDPO) was separated into olein and stearin by applying progressive freeze concentration (PFC) as an alternative method to replace the conventional fractionation process using coil crystallizer. Overall heat transfer coefficient (U) was analyzed from the process by varying different coolant temperature values since both of them are closely related each other. In this case, heat transfer efficiency depends strongly on crystal of stearin formed on the inner wall of cooled surface and is explained theoretically from that angle. At optimum flowrate, operation time and initial iodine value (IV), the best results were observed at 28ºC of coolant temperature where high IV of olein and effective partition constant (K) obtained were 55.8 wijs and 0.27 respectively. Meanwhile, the highest U obtained at coolant temperature 28oC same as result for process efficiency at 392.9183 W/m².K and time at 55 min.